Avaliação e melhoria do poder calorífico de biogás proveniente de resíduos sólidos urbanos - Okamura, Layssa Aline (2013)
Given the new global scenario turned to sustainable practices it is becoming a major focus of research the search for technologies that use renewable resources reducing or eliminating the production of environmental pollutants and contaminants in energy production process. This project focused on the purification of biogas in Curitiba’s closed landfill of to evaluate its use for energy production, aiming to improve its calorific value. During the study, a calorimeter was developed and optimized to evaluate the calorific value of the biogas. For results comparison, analyses were made to determinate the concentrations of methane, carbon dioxide, ammonia and hydrogen sulfide using a commercial kit for analysis of biogas. Landfill biogas sampling and analysis were conducted at two sites where the waste was confined at different times. We identified significant differences in the levels of methane and hydrogen sulfide in the analyzed gases. Biogas purification was performed by applying columns packed with lead acetate solution, sodium hydroxide solution, silica gel and activated carbon. A higher efficiency of biogas purification (145%) was attained with a lower initial methane content (23%). The use of saturation indicators proved to be very interesting in the use of purification column, since the saturation could be determined visually. With the purification percentage calculated, it was estimated the energy production, revenue through energy sale and costs related to the purification process. Through this estimation it is possible to note that the profits from the electricity produced sale would be sufficient to meet the costs of the purification process application.